Omega-3 Polyunsaturated Fatty Acids Enhance Neuronal Differentiation in Cultured Rat Neural Stem Cells - Masanori Katakura; Michio Hashimoto; Toshiyuki Okui; Hossain Md Shahdat; Kentaro Matsuzaki; Osamu Shido (Stem Cells International)
Polyunsaturated fatty acids (PUFAs) can induce neurogenesis and recovery from brain diseases. However, the exact mechanisms of the beneficial effects of PUFAs have not been conclusively described. We recently reported that docosahexaenoic acid (DHA) induced neuronal differentiation by decreasing Hes1 expression and increasing p27kip1 expression, which causes cell cycle arrest in neural stem cells (NSCs). In the present study, we examined the effect of eicosapentaenoic acid (EPA) and arachidonic acid (AA) on differentiation, expression of basic helix-loop-helix transcription factors (Hes1, Hes6, and NeuroD), and the cell cycle of cultured NSCs. EPA also increased mRNA levels of Hes1, an inhibitor of neuronal differentiation, Hes6, an inhibitor of Hes1, NeuroD, and Map2 mRNA and Tuj-1-positive cells (a neuronal marker), indicating that EPA induced neuronal differentiation. EPA increased the mRNA levels of p21cip1 and p27kip1, a cyclin-dependent kinase inhibitor, which indicated that EPA induced cell cycle arrest. Treatment with AA decreased Hes1 mRNA but did not affect NeuroD and Map2 mRNA levels. Furthermore, AA did not affect the number of Tuj-1-positive cells or cell cycle progression. These results indicated that EPA could be involved in neuronal differentiation by mechanisms alternative to those of DHA, whereas AA did not affect neuronal differentiation in NSCs.